2015
DOI: 10.3390/ijerph120404128
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Variations in Physico-Chemical and Microbiological Characteristics of Mvudi River, South Africa

Abstract: Surface water has been a source of domestic water due to shortage of potable water in most rural areas. This study was carried out to evaluate the level of contamination of Mvudi River in South Africa by measuring turbidity, electrical conductivity (EC), pH, concentrations of nitrate, fluoride, chloride, and sulphate. E. coli and Enterococci were analysed using membrane filtration technique. Average pH, EC and Turbidity values were in the range of 7.2–7.7, 10.5–16.1 mS/m and 1.3–437.5 NTU, respectively. The me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 19 publications
4
30
0
Order By: Relevance
“…Chaurasia and Tiwari (2011) in a study on the water quality on Rapti River in India reported that due to discharge of sugar factories wastewater into this river, the water quality was reduced (Chaurasia and Tiwari 2011). Edokpayi et al (2015) evaluated the water quality of Mvudi River in South Africa and compared the bacterial count in two dry and wet seasons. Their results showed that there was no significant difference in E. coli number between two seasons (Edokpayi et al 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chaurasia and Tiwari (2011) in a study on the water quality on Rapti River in India reported that due to discharge of sugar factories wastewater into this river, the water quality was reduced (Chaurasia and Tiwari 2011). Edokpayi et al (2015) evaluated the water quality of Mvudi River in South Africa and compared the bacterial count in two dry and wet seasons. Their results showed that there was no significant difference in E. coli number between two seasons (Edokpayi et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Edokpayi et al (2015) evaluated the water quality of Mvudi River in South Africa and compared the bacterial count in two dry and wet seasons. Their results showed that there was no significant difference in E. coli number between two seasons (Edokpayi et al 2015). Similarly, in the present study, there was no significant difference between four seasons in case of E. coli count.…”
Section: Discussionmentioning
confidence: 99%
“…It falls in the Lowveld of Limpopo Province, which forms part of the greater Limpopo River Basin with an elevation of 546 m above sea level [18,19]. It has a semi-arid climate, which is classified as humid subtropical with a subtropical dry forest biozone.…”
Section: Study Areamentioning
confidence: 99%
“…A report by the South African Council for Scientific and Industrial Research clearly showed that almost 2.11 million people in South Africa lack access to any safe water infrastructure. The consumption of water from such unimproved sources without treatment constitutes a major public health risk [26].…”
Section: Introductionmentioning
confidence: 99%